Factors associated with activities of daily living among the disabled elders with stroke - Li Pei; Xiao-Ying Zang; Yan Wang; Qian-Wen Chai; Jun-Ying Wang; Chun-Yan Sun; Qing Zhang (Elsevier, 2016)
Objective: To determine the factors associated with activities of daily living (ADL) among the disabled elders post-stroke. Methods: A total of 158 patients were chosen from community health service stations in eighteen regions of Tianjin city by convenience sampling from March to November in 2013. The Barthel Index (BI) and the short-form mini-nutritional assessment (MNA-SF) were used to evaluate the ADL, the nutritional status respectively. Statistical analysis was performed using independent sample t-test, one-way ANOVA, Pearson correlation and multiple linear regression analysis. Barthel ADL index was the main outcome. Results: The mean score of ADL was 50.50 ± 27.125. The multiple linear regression showed that the factors which had significant impact on ADL were stroke frequency, types of stroke, nutritional status, financial status, and age. Conclusions: Disabled elders with recurrent strokes, hemorrhagic stroke, dependent financial resources, older age, worse nutritional status and living with family had poorer stroke-related outcome. Healthcare providers can discover the high-risk groups of disability and implement individualized preventive interventions in accordance with the related factors. Keywords: Activities of daily living, Disabled persons, Frail elders, Stroke